Regulation of microgeneration and microgrids - Costa, Paulo Moisés (2017)
The concept of microgrid (μGrid) has been emerging as a way to integrate microgeneration (μG) in low-voltage (LV) networks and simultaneously improve its potential benefits. Technical requirements to connect μgrids to LV networks have been studied in order to make this concept technologically feasible and safe to operate. However, the regulatory framework for economic integration of μG and μGrids on distribution systems, despite being crucial, is still an open issue. The main purpose of this paper is to contribute for the development of an appropriate economic regulation framework that removes the barriers to μG and μGrid development. To do so, the relevant costs and benefits resulting from the establishment of μG and μGrid are identified and a methodology for sharing those costs and benefits among the involved economic agents is presented. The only pre-requisite of such a methodology is the existence of a net benefit to all economic agents.